Plasma Sphingolipids and Subclinical Atherosclerosis – Novel Associations Uncovered by a Large-scale Lipidomic Analysis (P18-129-19). (13th June 2019) - Hoong, Jowy Seah Yi; Chew, Wee Siong; Torta, Federico; Ji, Shanshan; Choi, Hyungwon; Begum, Husna; Sim, Xueling; Khoo, Chin Meng; Khoo, Eric Yin Hao; Ong, Wei-Yi; Wenk, Markus; Tai, E Shyong; et al.
Abstract: Objectives: Sphingolipids (SP) are a diverse class of heterogenous lipids that includes ceramides, sphingomyelins, and glycosphingolipids. Many SPs have diverse roles in cell functions including cell growth, inflammation and angiogenesis, and previous studies suggest that SPs may also be involved in the pathogenesis of cardiovascular diseases. We aimed to identify plasma SPs and subsequently evaluate associations between plasma SPs and subclinical atherosclerosis in a subset of the Multiethnic Cohort of Singapore with the goal of uncovering novel biomarkers predictive of heart disease. Methods: We conducted a lipidomics evaluation of 103 molecularly-distinct SPs in the plasma of 559 Singaporeans aged 50 years and above using electrospray ionization mass spectrometry coupled with liquid chromatography. All participants did not have a history of diabetes, heart disease, stroke or cancer at baseline, and completed a detailed health screening that evaluated risk factors for cardiovascular disease including computed tomography scans of the abdomen and coronary arteries. Multivariable logistic regression models were used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for associations between SPs and subclinical atherosclerosis (defined as coronary artery calcium score ≥ 100). Results: Ceramides (Cer), particularly those with a d16:1 or d18:1 backbone, were directly associated with higher risk of subclinical atherosclerosis whereas a small number of monohexosylceramides (MHCer), dihexosylceramides (DHCer) and sphingomyelins (SM) with a d18:2 sphingoid backbone were inversely associated. However most associations were attenuated after adjusting for conventional cardiovascular risk factors, including blood lipid (low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, triglycerides) concentrations and glycemic markers, suggesting that the associations may be mediated by these risk factors. Conclusions: High-throughput lipidomics may uncover novel sphingolipids predictive of heart disease. Characterization of these lipid species could provide insights into disease etiology. Funding Sources: This work was supported by the National University Health System and the National Research Foundation Investigatorship grant. Supporting Tables, Images and/or Graphs: